Abordagem investigativa em botânica, com identificação de espécies de plantas por estudantes do ensino médio - Vilmara Pereira Freire Ribeiro (2020)
Many students’ lack of interest in botany teaching is current in biology, especially in high school. The terms used in the study of plants are difficult to understand and contribute to distance many students from this approach. According to the National Curriculum Parameters for High School, each area of knowledge should promote contextualized, practical knowledge compatible with current needs. This may contribute to developing the reasoning, interpretations, investigations, and questions by some students, providing active learning beyond memorization. Thus, in this work, a didactic sequence was proposed to arouse students’ interest in botany and provide meaningful learning on the topic. To achieve the aims, an inquiry-based teaching sequence was developed, involving practical classes in non-formal spaces, collections of botanical materials, and smartphones to obtain photographs, aiming to identify plant species by students. Initially, a diagnostic evaluation was carried out, with a test with motivating questions about the theme to verify the students’ previous knowledge. Students collected botanical materials during practical activities, photographed the plants, and recorded the data observed in a field diary, which were used to identify the plants. At the end of the process, the test was reapplied. An interactive debate was held with the research participants to verify the importance of the practices carried out in the students’ understanding and interest in botany. The data and materials obtained in the practical activities were used in a digital catalog, a mini herbarium, and a fruit collection. During the debate and through records in the field diary, the students participating in the research expressed the importance of developing practical activities in teaching and learning botany. They felt autonomous and motivated during the process. In the end, there was a significant increase in students’ knowledge about plant groups, about plant species, known by their common names, and about the characteristics that help to identify plants at the appropriate level for high school students.